Consequences of hybridization and heterozygosity on plant vigor and phenotypic stability. (March 2015) - Fridman, Eyal
Highlights: Plant populations are diversifying and hybridization often leads to hybrid vigor. Single overdominant genes are not the major source for heterosis in hybrids. Biochemical considerations support negative consequences of local heterozygoity. Local vs. overall heterozygosity may be associated with reduced phenotypic stability. Destabilization by local heterozygosity is expected for self-fertilizing plants. Abstract: The genomic makeup and phenotypes of plants are diversifying, in part due to artificial or natural selection in agricultural and natural environments. Utilization of these variations to enhance crop productivity requires an understanding of the relationships between genotype and phenotype in inbreds and hybrids derived from crosses between these populations. This review highlights recent studies on hybrid vigor (heterosis) and the related phenomenon of hybrid weakness – two types of non-additive inheritance. Heterosis is a phenomenon whereby the phenotype of first-generation hybrids is superior to that of their parents. Intralocus interactions between alleles, complementation of dominant alleles, or inter-loci epistatic interactions are genetic mechanisms that may cause non-additive phenotypic inheritance in hybrids. However, there are different views on what portion of the heterotic variation is modulated by each of these mechanisms. Another aspect of plant vigor is phenotypic stability or robustness in different environments and how this is influenced by gene heterozygosity. Hybrids are not necessarily more phenotypically stable than inbreds since local heterozygosity might be associated with negative effects on biochemical activities. This review integrates genetic and biochemical considerations to illustrate how these relationships may be tightly linked with breeding system and sequence divergence.